Reimagining Internet Geographies: A User-Centric Ethnological Mapping of the World Wide Web. Issue 3 (4th March 2016) - Wu, Angela Xiao; Taneja, Harsh
Abstract: We propose a new user-centric imagery of the WWW that foregrounds local usage and its shaping forces, in contrast to existing imageries that prioritize Internet infrastructure. We construct ethnological maps of WWW usage through a network analysis of shared global traffic between 1000 most popular websites at 3 time points and develop granular measures for exploring global participation in online communication. Our results reveal the significant growth and thickening of online regional cultures associated with the global South. We draw attention to how local cultural identity, affirmative state intervention and economic contexts shape regional cultures on the global WWW.